Alternative paradigms and the study and practice of performance management and evaluation - McKenna, Stephen; Richardson, Julia; Manroop, L. (2011)
Performance management and evaluation (PME) is a well-established element of any organizational system of human resource management. However, the research field for PME is dominated by a one-dimensional approach located within positivist ontology. This paper explores and compares this positivist approach to PME with approaches located in other paradigms, more specifically interpretivism and critical theory. The paper argues that paradigmatic diversity in the study of PME would contribute a multidimensional, more sophisticated and nuanced approach. While research on PME within interpretivist and critical paradigms has been conducted over many years it is largely ignored or rejected in North America where a focus on managerialist prescriptions drives the research agenda. This paper calls for innovation through paradigmatic diversity in PME research and scholarship rather than further, incremental development of prescriptive models.